Drug-based mobilisation of mesenchymal stem/stromal cells improves cardiac function post myocardial infarction - Todorova,VB; Baxan,N; Delahaye,M; Harding,SE; Rankin,SM (Disease Models and Mechanisms, 2023)
There is an unmet need for treatments that prevent the progressive cardiac dysfunction following myocardial infarction. Mesenchymal stem/stromal cells (MSCs) are under investigation for cardiac repair; however, culture expansion prior to transplantation is hindering their homing and reparative abilities. Pharmacological mobilisation could be an alternative to MSC transplantation. Here, we report that endogenous MSCs mobilise into the circulation at day 5 post myocardial infarction in male Lewis rats. This mobilisation can be significantly increased by using a combination of the FDA-approved drugs mirabegron (β3-adrenoceptor agonist) and AMD3100 (CXCR4 antagonist). Blinded cardiac magnetic resonance imaging analysis showed the treated group to have increased left ventricular ejection fraction and decreased end systolic volume at 5 weeks post myocardial infarction. The mobilised group had a significant decrease in plasma IL-6 and TNF-α levels, a decrease in interstitial fibrosis, and an increase in the border zone blood vessel density. Conditioned medium from blood-derived MSCs supported angiogenesis in vitro, as shown by tube formation and wound healing assays. Our data suggest a novel pharmacological strategy that enhances myocardial infarction-induced MSC mobilisation and improves cardiac function after myocardial infarction.